Impact of the final agitation system in the irrigant diffusion inside the root canal: A micro-CT analysis - de Moraes Cruz, Victor; Duarte, Marco Antônio Húngaro; Kato, Augusto Shoji; Alcalde, Murilo Priori; Coelho, Letycia Accioly Simões; Tanomaru-Filho, Mario [UNESP]; Gavini, Giulio; Vivan, Rodrigo Ricci (Wiley, 2023)
This study evaluated, through micro-computed tomography (micro-CT), the volume of irrigant diffusion by different techniques of final agitation. Sixty mesiobuccal canals were scanned in a micro-CT and standardised according to the volume. They were instrumented with the MTwo 40/04 system and using the Terebrix 35 contrast solution as irrigant, were divided into six groups (n = 10): Conventional irrigation with syringe and needle (CI), EndoActivator (EA), EasyClean (EC), RinsEndo (RE), Utrasonic agitation (UI) and XP-Clean (XP). A second micro-CT scan was performed and the total irrigant volume and in the final 3 mm apical were determined. The data were analysed using the Anova, Kruskal–Wallis and Dunn tests (p < 0.05). UI and XP showed a higher percentage of total diffusion than CI, EA and RS groups (p < 0.05). In apical diffusion, there was no significant difference between groups (p > 0.05). The final agitation system increases the diffusion of irrigating agents inside the root canal.
Keywords: cleaning; endodontics; irrigant activation; root canal irrigants; ultrasonic activation